Penyusunan Instrumen Penilaian Hots dalam Pembelajaran IPS Sekolah Dasar - Rati Syafiana Putri; Wiwit Sanjaya; Yanti Fitria (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Social Science (IPS) is several integrated social sciences for teaching and educational purposes. The study aims to examine the HOTS assessment technique in social studies learning in elementary schools. The research applied descriptive method, where various literature reviews are used to describe the questions to get answers. The resultsishowed that the techniques for preparing HOTS-basedisocial research learning assessment tools included analyzing KD, compiling grids, choosing interesting situational stimuli, writing questions according to the question grid, determining answer keys for assessment, conducting qualitative analysis, and conducting quantitative analysis . Writing HOTS questions requires the question maker to be able to determineithe behavior to be measured based on the expected behavior, and in certain contexts to formulate the materialito be used as the basis for the questions.